HUBUNGAN ANTARA PEMANFAATAN INTERNET SEBAGAI MEDIA PEMBELAJARAN DENGAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGERI 1 PALEMBANG - Ema Indira Sari; Ismail Sukardi; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
The research study was motivated by the lack of adequate facilities in the use of the internet in the classroom, besides the limitations in accessing the internet due to students abusing it for other purposes than as a search for learning material, as well as the lack of enthusiasm of students in following the learning process in class. This study aims to determine the use of the internet as a medium of learning, to motivate students and find out whether or not there is a significant relationship between the use of the internet as a learning medium with learning motivation. This research uses quantitative research that uses quantitative descriptive approach, the sample taken by the researcher is random sampling. Data obtained using a questionnaire and documentation. Further analysis with the collected data is then recapitulated after the data has been collected from various sources then the data is processed by analyzing using descriptive quantitative data analysis techniques. The results of the study concluded that the use of the internet as a medium of learning in the subjects of the Islamic Morals was moderate. This can be proven from the results of the distribution of questionnaires to 90 respondents who were used as research samples. Student learning motivation in the subjects of the Islamic Morals is moderate. This can be proven from the results of the distribution of questionnaires to 90 respondents who were used as research samples. There is a relationship between the use of the internet as a learning medium with student learning motivation. This is based on the results of the calculation of product moment correlation so that the obtained rxy value of 0.211 and rtable value at a significance level of 5% is equal to 0.207.